Oldest estimated age for Sphyrna mokarran (Carcharhiniformes: Sphyrnidae) in the Mexican Pacific - Tovar-Ávila, Javier; Gallegos-Camacho, Rodney (HIDROBIOLÓGICA, 2016)
The estimated age (around 45 years) from vertebral growth band counts for the largest Sphyrna mokarran caught in the Gulf of California and Central Mexican Pacific in the last decades, locates it as the oldest elasmobranch reported to date in Mexican Pacific waters. The specimen studied was a mature female of approximately 550 kg of total weight and 424 cm of total length, caught by artisanal fishermen using longlines south of the archipelago of Islas Marías on November 11th 2010. The distance between growth bands showed fast growth during the first 10 years. Growth bands after the age of 38 were only visible in the corpus calcareum, though difficult to separate and count. The age estimated in the present study was similar to the maximum age reported for the species in the Atlantic Ocean and Gulf of Mexico, confirming the species as long lived.